Estimation of Population Parameters and Stock Assessment of Mastacembelus armatus in the Taojiang River, Xinfeng County, Jiangxi Province, China - Bin, Wu; Haihua, Wang; Benhe, Ma; Xiandong, Xu; Qingxiang, Zeng (Indian journal of animal research, 2022)
A study was conducted to investigate the growth parameters, mortality and recruitment pattern of Mastacembelus armatus collected in the Taojiang River fish landing site, Xinfeng County. M. armatus were collected from March, 2018 to February, 2019. Growth parameters, asymptotic length (L¥) = 58.8cm and growth coefficient (k) = 0.13 year-1. Growth performance index(Ø2 ) =2.65, total mortality (Z) = 0.75 year-1, natural mortality (M) = 0.32 year-1, fishing mortality (F) = 0.43 year-1 and exploitation rate (E) = 0.57year-1.The estimated exploitation rate (E) has slightly exceeded the optimum value of E indicating this species was over exploited mainly due to fishing in the study area. The exploitation ratios were computed as Emax= 0.59, E10= 0.45, E50= 0.31. The length at first capture at 50%, (Lc) was 19.51 cm. The Steady biomass also increased with length class until 36.0-36.9 cm and the total steady state biomass was found to be 19.12 tons.